Beneficial Autoimmunity at Body Surfaces – Immune Surveillance and Rapid Type 2 Immunity Regulate Tissue Homeostasis and Cancer - Dalessandri, Tim; Strid, Jessica (Frontiers in Immunology, 2014)
Epithelial cells line body surface tissues and provide a physicochemical barrier to the external environment. Frequent microbial and non-microbial challenges such as those imposed by mechanical disruption, injury or exposure to noxious environmental substances including chemicals, carcinogens, ultraviolet-irradiation or toxins cause activation of epithelial cells with release of cytokines and chemokines as well as alterations in the expression of cell surface ligands. Such display of epithelial stress is rapidly sensed by tissue resident immunocytes, which can directly interact with self-moieties on epithelial cells and initiate both local and systemic immune responses. Epithelial cells are thus key drivers of immune surveillance at body surface tissues. However, epithelial cells have a propensity to drive type 2 immunity (rather than type 1) upon non-invasive challenge or stress – a type of immunity whose regulation and function still remain enigmatic. Here we review the induction and possible role of type 2 immunity in epithelial tissues and propose that rapid immune surveillance and type 2 immunity are key regulators of tissue homeostasis and carcinogenesis.